Main directions of modern enterprise strategy formation - Kalaman, Olga; Udovitsa, Oleg (Ekonomìka, ekologìâ, socìum, 2018)
Introduction. Today in Ukraine there is a situation that creates an environment of "public interest" in approaches to modeling the main areas of strategic management and its content. Inaccurate perception of approaches to the "strategy" concept content significantly changes the possibility of its effective implementation at the state and economic levels. Therefore, it is logical to arise the necessity of studying the directions of forming a strategy and the possibility of applying the theory of strategic management in modern domestic enterprises. Aim and tasks. The article purpose is to determine the basic approaches to the formation of the modern enterprise development strategy, which is subject to the study of the main directions of its formation. The systematic basis for such systematization was systemic, reproductive, dialectical, and general scientific approaches. Research results. It has been established that the "action" approach as the leading methodology for the strategy development implies the relevance of the activity category with the concepts of "needs", "interests", "motives", "goals", "reflection (assessment)," "self-development". A system approach involves considering a strategy as a system that has a certain structure and interconnection within its individual components. Formation and strengthening market relations stimulates the application of new approaches and forms in management, changes (sometimes cardinally) the nature of the tasks to be solved and methods for their achievement, as well as the development of a strategy. The development of a clearly formulated strategy and the definition of organic development goals is a consequence of the external conditions manifestation of the company's existence, for example, the conditions of macroeconomic instability, the complexity of the relationship between the economic and political environment. To clearly formulate a strategy for the enterprise in accordance with the current economic situation, to outline the ways of its implementation and, if possible, to evaluate the expected result, a manager is required to possess creativity, knowledge and experience, intuition in a unified approach to formulating strategic prospects for the operation and development of the enterprise. Conclusion. For Ukrainian enterprise management system, the main task is not the prompt response to the current changes in the environment. They are the strategic vision formation of the future enterprise, the development of a flexible and viable progress strategy, the prediction of tactical and strategic threats for the enterprise, its timely elimination, and the practical use of strategic management idea for sustainable development.